2022
DOI: 10.3389/fimmu.2022.803854
|View full text |Cite
|
Sign up to set email alerts
|

The Antibody Assay in Suspected Autoimmune Encephalitis From Positive Rate to Test Strategies

Abstract: ObjectiveThe aim of this study was to analyze the positive rate and test strategies of suspected autoimmune encephalitis (SAE) based on an antibody assay.MethodsPatients who were diagnosed with suspected autoimmune encephalitis in Guizhou Province between June 1, 2020, and June 30, 2021 and who had anti-neuronal autoantibodies detected by Guizhou KingMed Diagnostics Group Co., Ltd. were included in this study. The positive rate and the test strategies were analyzed based on the results of the anti-neuronal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 32 publications
3
9
2
Order By: Relevance
“…CASPR2 antibodies in CSF and serum have diagnostic value for identifying individuals with CASPR2 antibody-associated AEs [ 7 , 8 , 46 , 47 ]. Since serum CASPR2 antibodies are common in pediatric AE patients, the detection rate in CSF is low [ 48 ]. Therefore, we need to pay more attention to the diagnostic value of serum antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…CASPR2 antibodies in CSF and serum have diagnostic value for identifying individuals with CASPR2 antibody-associated AEs [ 7 , 8 , 46 , 47 ]. Since serum CASPR2 antibodies are common in pediatric AE patients, the detection rate in CSF is low [ 48 ]. Therefore, we need to pay more attention to the diagnostic value of serum antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from each patient in our centre were sent to Guangzhou KingMed Diagnostics Group Co., Ltd for testing. 3 Positive results were evaluated at least in duplicate on the samples. The intensity of the surface immunofluorescence, which was directly compared to control samples and samples lacking transfected cells, was used by two independent, masked assessors to determine whether a sample was positive or negative.…”
Section: Detection Of Ae-absmentioning
confidence: 99%
“…2 Since the first study on antibody (specifically immunoglobulin-G [IgG]) biomarkers was published in 2007, autoimmune encephalitis research has rapidly advanced.Forty intracellular antibodies and more than 20 extracellular antibodies have been identified so far. 3 Recently, a large cohort study has shown a seroprevalence of 3.6% for autoimmune encephalitis antibody biomarkers (AE-Abs) in adults, with the most common AE-Abs being N-methyl-Daspartate receptor (NMDAR-IgG), glutamic acid decarboxylase 65 (GAD65-IgG), and leucine-rich glioma-inactivated 1 (LGI1-IgG). 4 Neuronal antibodies identify autoimmune encephalitis subtypes and help clinicians identify cases with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2007, an increasing number of new specific anti-neuronal antibodies have been reported, and the study of AE has markedly expanded; in total, more than twenty extracellular antibodies and forty intracellular antibodies have been identified (2,3). The estimated prevalence of AE in the United States and China is 0.8/ 100,000 and is increasing rapidly (4,5). Previous studies have demonstrated that approximately 50% of AE patients require intensive care unit (ICU) treatment (6).…”
Section: Introductionmentioning
confidence: 99%